In vitro effect of polyestradiol on lecithin: cholesterol acyltransferase in rat blood (Revista Española de Fisiología, 1982)
The in vitro effect of increasing amounts of polyestradiol on LCAT activity was measured in plasma of male and female rats.The results showed that the hormone decreased the enzyme activity in both sexes.The concentration of polyestradiol required for this inhibitory effect was greater in male than in female plasma.No correlation was found between LCAT activity and polyestradiol concentration.